Security impact of cross-site scripting vulnerabilities on web applications and their awareness - Hydara, Isatou; Md Sultan, Abu Bakar; Zulzalil, Hazura; Admodisastro, Novia Indriaty (Kalahari Journals, 2022)
Cross-site scripting vulnerabilities exist in many web applications. They are a security problem that has affected web applications for the last two decades as well as the mobile version of web applications more recently. They can seriously affect web application users with the loss of their private data to web hackers. In addition, other security problems can occur including denial of service attacks that can shut down networks, phishing attacks that enable theft of user data, and the exposure to other similar threats. The previous proposed solutions to cross-site scripting vulnerabilities mostly focused on mitigating these vulnerabilities on traditional web applications. However, this is changing as more researchers are also including the mobile versions in their proposed solutions. This is because more people are using their mobile phones to open web applications and they face an increasing threat of cross-site scripting attacks and the possibility of being victimized. In this paper, we explore and discuss the security impact that cross-site scripting vulnerabilities have in modern web applications, and the importance of raising awareness of these vulnerabilities, not only within the technology industry but also to the public.